Relationship between bench press strength and punch performance in male professional boxers - López-Laval, I.; Sitko, S.; Muñiz-Pardos, B.; Cirer-Sastre, R.; Calleja-Gonzalez, J. (The Journal of Strength and Conditioning Research, 2020)
This study investigated the relationship between punching performance and the velocity at which different loads were lifted during the bench press (BP) exercise in 12 professional boxers (age = 22.6 ± 4 years; height = 177.7 ± 5 cm; body mass 70.6 ± 6.43 kg; years of boxing experience = 6.5 ± 3.5 years; weight class = from light to super welterweight). To determine the maximal punching velocity (PVmax) during both rear arm (RA) and lead arm (LA) punching, an accelerometer (Crossbow; Willow Technologies, Sussex, United Kingdom) was placed inside the boxing glove while executing 3 jabs at a maximal velocity with each arm. Upper-body strength was assessed through the direct 1-repetition maximum (1RM) BP test, and the maximum velocity at different percentages of 1RM was obtained with a linear encoder. The main finding was that RA PVmax was correlated with the BP velocity at all submaximal intensities (p < 0.05). Nevertheless, LA PVmax did not correlate with BP velocity at any intensity. When the correlated BP submaximal intensities were introduced in linear regression models, the velocity at 80% 1RM was the only predictor of RA PVmax (r2 = 0.75; p < 0.01) in professional boxers. Additional body mass adjustment to the regression model significantly affected the predictive value (r2 = 0.65; p < 0.005). Results encourage coaches and trainers to use BP exercise with high loads (i.e., 80% of 1RM) because this could be a reliable predictor of performance during the specific boxing action. Future research is needed to determine exercises and intensities that could explain LA PVmax because significant associations were not found.